Structural Health Monitoring strategies based on the estimation of modal parameters. (2017) - Lorenzo, Emilio Di; Manzato, Simone; Peeters, Bart; Marulo, Francesco; Desmet, Wim
Abstract: Rotating machines have always been used in a wide variety of industrial applications. Nowadays it is very difficult to find machines or mechanical systems which do not have any rotating component such as gears, bearings, shafts, wheels and so on. Wind turbines, gearboxes, combustion and electrical engines, generators and gas turbines are just few examples of objects with several rotating substructures. These machines face very complex and non-linear conditions during their operating cycles. they are often subjected to the fatigue problem and it is fundamental to detect faults or damages well in advance in order to reschedule the maintenance cycles. This is especially true for big machines (i.e. wind turbines) where the maintenance costs are a huge part of the total costs. Structural Health Monitoring (SHM) is a technology which is able to provide a continuous indication of the health and the reliability of the structure along its lifecycle. A damage detection technique is an essential part of any SHM system. Its scope consists in the identification of some structural and environmental parameters which have to be monitored regularly during the operation of the machine. This technique should be able to distinguish if the damage is present or not in the structure, but it should also locate and quantify the same damage. A damage can be seen as a change in material and/or geometric properties of a structure, including variation of boundary conditions and structural connections. Several studies have been performed and two different SHM strategies have been defined. The first one is based upon the whirling phenomenon. The whirling modes are the most identifiable modes in operating conditions and they appear to be very sensitive to changes of stiffness. Their amplitude and phase can be used as damage indicators because they allow to identify the loss of isotropy in the rotor. A second parameter which is quite sensitive even to small changes of stiffness is the curvature of the mode shapes. For beam-like structure it has been demonstrated being a very good damage indicator. Several simulations have been run together with some experimental validation on a wind turbine blade.